Forward genetic screen using a gene-breaking trap approach identifies a novel role of grin2bb-associated RNA transcript (grin2bbART) in zebrafish heart function - Angom, Ramcharan Singh; Joshi, Adita; Patowary, Ashok; Sivadas, Ambily; Ramasamy, Soundhar; K. V., Shamsudheen; Kaushik, Kriti; Sabharwal, Ankit; Lalwani, Mukesh Kumar; K., Subburaj; Singh, Naresh; Scaria, Vinod; et al. (Frontiers in Cell and Developmental Biology, 2024)
LncRNA-based control affects cardiac pathophysiologies like myocardial infarction, coronary artery disease, hypertrophy, and myotonic muscular dystrophy. This study used a gene-break transposon (GBT) to screen zebrafish (Danio rerio) for insertional mutagenesis. We identified three insertional mutants where the GBT captured a cardiac gene. One of the adult viable GBT mutants had bradycardia (heart arrhythmia) and enlarged cardiac chambers or hypertrophy; we named it 'bigheart'. Bigheart mutant insertion maps to grin2bb or N-methyl D-aspartate receptor (NMDAR2B) gene intron 2 in reverse orientation. Rapid amplification of adjacent cDNA ends analysis suggested a new insertion site transcript in the intron 2 of grin2bb. Analysis of the RNA sequencing of wildtype zebrafish heart chambers revealed a possible new transcript at the insertion site. As this putative lncRNA transcript satisfies the canonical signatures, we called this transcript grin2bb associated RNA transcript (grin2bbART).Using in situ hybridization, we confirmed localized grin2bbART expression in the heart, central nervous system, and muscles in the developing embryos and wild-type adult zebrafish atrium and bulbus arteriosus. The bigheart mutant had reduced Grin2bbART expression. We showed that bigheart gene trap insertion excision reversed cardiacspecific arrhythmia and atrial hypertrophy and restored grin2bbART expression.Morpholino-mediated antisense downregulation of grin2bbART in wild-type zebrafish embryos mimicked bigheart mutants; this suggests grin2bbART is linked to bigheart. Cardiovascular tissues use Grin2bb as a calcium-permeable ion channel. Calcium imaging experiments performed on bigheart mutants indicated calcium mishandling in the heart.The bigheart cardiac transcriptome showed differential expression of calcium homeostasis, cardiac remodeling, and contraction genes. Western blot analysis highlighted Camk2d1 and Hdac1 overexpression. We propose that altered calcium activity due to disruption of grin2bbART, a putative lncRNA in bigheart, altered the Camk2d-Hdac pathway, causing heart arrhythmia and hypertrophy in zebrafish.